2007
DOI: 10.1038/sj.ijir.3901631
|View full text |Cite
|
Sign up to set email alerts
|

Daily use of phosphodiesterase 5 inhibitors for erectile dysfunction and lower urinary tract symptoms

Abstract: Erectile dysfunction is a prevalent disorder that not only affects men with the disorder but also their partners. Significant improvements in the sexual health of these couples have been achieved with the introduction of phosphodiesterase 5 (PDE5) inhibitors. Currently PDE5 inhibitors are used on an on-demand basis. New evidence regarding the effects of PDE5 inhibitors on the underlying pathophysiologic processes that cause erectile dysfunction have sparked interest in the continuous dosing of these medication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2010
2010

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Padma-Nathan described for the first time the role of nightly assumption of PDE5-I after BNSRRP, and he demonstrated that nightly administration of sildenafil increased the return to spontaneous erection sevenfold compared with placebo (4% vs. 27%) [24]. Recently, Pimentel suggested that post-prostatectomy and LUTS patients are those who could most likely benefit from daily dosing, even if final evidence is still lacking [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Padma-Nathan described for the first time the role of nightly assumption of PDE5-I after BNSRRP, and he demonstrated that nightly administration of sildenafil increased the return to spontaneous erection sevenfold compared with placebo (4% vs. 27%) [24]. Recently, Pimentel suggested that post-prostatectomy and LUTS patients are those who could most likely benefit from daily dosing, even if final evidence is still lacking [25].…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that vardenafil can induce relaxation of bladder with the consequent reduction of detrusor pressure and an increase of cystometric capacity [22]. The remarkable improvement in clinical symptoms without significant change in urinary flow rate after PDE5-I administration in men with BPH [4][5][6] can be justified by a strong activity on the bladder wall, with minimal action on the prostate [25]. The results of the present study demonstrate for the first time that the PDE5-I activity on LUTS can also be expressed in the absence of the prostate.…”
Section: Discussionmentioning
confidence: 99%